KAJIAN EKOLOGI DAN STATUS KEBERADAAN KOMODO (Varanus komodoensis) DI PULAU PADAR TAMAN NASIONAL KOMODO - Abdul Haris Mustari; Hendrikus R. Siga; Trisna Noviandi; Ayatullah .; Zainuddin . (Department of Forest Resources Conservation and Ecotourism - IPB University, 2010)
The existence of the giant reptile, komodo (Varanus komodoensis) on Padar has long been debated by management authorities, scientists, local people and local govenment. Does komodo species still exists on the island or are they extict locally?. This study was conducted in November 2006 to reveal the ecological conditions of Padar Island including the existence of komodo and its potential preys especially big mammals. As two its adjacent bigger islands, Komodo and Rinca, Padar is dominated by savanna (70%) with scattered green belts composed by limited species of trees on valleys, beaches and mangrove forests. Of the big mammals which were potential as komodos preys, Padar was only inhabited by timor deer, wild boar and long tailed macaque which is different from its neighbouring islands, Komodo and Rinca where there were timor deer, wild boar, water buffaloe, wild horse and long tailed macaque. Population of timor deer on Padar was estimated to be 60-100 individuals which was far below the former population that had been recorded 800-1000 individuals. During the study, komodo could not be found on the island both direct and indirect encounters supporting the previous studies and information from the field rangers that komodo is now extict on Padar. Increasing population of timor deer and wild boar is one of the key factors determining the successfull of reintroducing komodo on the island. Keywords : Padar, komodo, prey, extinct, reintroduction